HISTORICAL LEARNING THROUGH THE HISTORICAL THINKING LEARNING MODEL (MPBH) BASED ON ISSUE CENTERED HISTORY BRINGS STUDENTS CAN THINK CRITICAL THINKING REALITY AND EXPECTATIONS - Mohamad Zaenal Arifin Anis; fitri mardiani; Erlina Wiyanarti (JURNAL SOCIUS, 2021)
The phenomenal development of history learning in developed countries has made history education experts in Indonesia train students to think historically and believe that learning history must be based on historical central issues. However, the implementation of historical thinking is based onissuehistorical centre as a powerful way to achieve critical historical learning is not without challenges. Many historical education experts admit that historical thinking is the best way to teach students to learn the critical history and be able to relate problemscontemporaryto historical phenomena to carry out successfully. This study aims to investigate the effectiveness of the learning model think historically (MPBH) based issue central history in the European History course. Data obtained from 2 classes with a population of 70 people. This study uses a quantitative approach with a quasi-experimental method. The research findings are significant differences between the experimental and control classes in improvement ability think critical student. Conclusione ffectiveness MPBH based on the central historical issue in this research has not been able to generalize still needed to expand the research by increasing the population and a wider area.